Dose–response plasma appearance of coffee chlorogenic and phenolic acids in adults. Issue 2 (4th September 2013) - Renouf, Mathieu; Marmet, Cynthia; Giuffrida, Francesca; Lepage, Mélissa; Barron, Denis; Beaumont, Maurice; Williamson, Gary; Dionisi, Fabiola
<x xml:space="preserve">Abstract</x> Scope Coffee contains phenolic compounds, mainly chlorogenic acids (CGAs). Even though coffee intake has been associated with some health benefits in epidemiological studies, the bioavailability of coffee phenolics is not fully understood. Objective and study design We performed a dose–response study measuring plasma bioavailability of phenolics after drinking three increasing, but still nutritionally relevant doses of instant pure soluble coffee. The study design was a one treatment (coffee) three‐dose randomized cross‐over design, with a washout period of 2 wks between visits. Results CGAs, phenolic acids, and late‐appearing metabolites all increased with increasing ingested dose. Hence, the sum of area under the curve was significantly higher for the medium to low dose, and high to medium dose, by 2.23‐ and 2.38‐fold, respectively. CGAs were not well absorbed in their intact form, regardless of the dose. CGA and phenolic acids appeared rapidly in plasma, indicating an early absorption in the gastrointestinal tract. Late‐appearing metabolites were the most abundant, regardless of the dose. Conclusion This study confirmed previous findings about coffee bioavailability but also showed that coffee phenolics appear in a positive dose–response manner in plasma when drank at nutritionally relevant doses.